Mediterranean Diet: Origin History, Main Components, Evidence of Benefits and Feasibility to Adapt to the Russian Reality - D. U. Akasheva; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
An unhealthy diet takes the lead in the concept of cardiovascular risk factors. It contributes to the development of various so-called “alimentary-dependent” risk factors and conditions: overweight/obesity, hyperglycemia, high blood pressure and hypercholesterolemia. This, in turn, leads to high cardiovascular morbidity and mortality. Many ways to rationalize and improve nutrition have been suggested. But the supremacy in prevention of cardiovascular diseases over the past decades steadily belongs to the Mediterranean diet. The history of origin, its main components, as well as the studies in which its usefulness has been proven, became the subject of this review. In addition, issues of adaptation of the Mediterranean diet to the Russian reality are submitted for discussion.